PROBLEMATIKA PEMBELAJARAN BAHASA INDONESIA KELAS III DI SEKOLAH DASAR - Esty Setyo Utaminingsih; Sulasih Sulasih; Maria Ayu Puspita; Sri Sumartiningsih; Ahmad Fajar Habibi; Tri Mulyaningtiyas (Universitas Indraprasta PGRI, 2023)
This research examines further related problems or problems in learning Indonesian in class III at Gombang Blora State Elementary School. The research method used a qualitative research method with a descriptive approach. The sampling technique used total sampling, where the respondents were a teacher and all third-grade students. The results showed that there were several problems in learning the Indonesian language for third-grade elementary schools, which were divided into four, including (1) learning media which were limited to textbooks from the Ministry of Education, there was no innovation in teaching materials, (2) listening skills were still low, the concentration of students is not good, and the motivation of students is still lacking in participating in the learning process, (3) learning strategies are monotonous and not yet innovative so that students are easily bored and less interested, (4) the ability of teachers in delivering material. Based on the problems, it is necessary to innovate the delivery of learning material by the teacher.